Biorational management of yellow mite, Polyphagotarsonemus latus in jute - V, Ramesh Babu; Gotyal, B S; Satpathy, S; Sarma, K K; Selvaraj, K; Mitra, S (Indian Journal of Plant Protection, 2020)
Field experiment was conducted to study efficacy of biorational insecticides comprising of neem, spiromesifen and entomopathogenic fungi, Lecanicillium lecanii against yellow mite, Polyphagotarsonemus latus infesting jute at two different locations for two successive cropping seasons. A total of seven treatments were imposed at various dosages and in combination thereof. Treatments imposed with spray application of spiromesifen 240 SC @ 0.7 ml/lit at 35 DAS & 50DAS and spiromesifen 240 SC @ 0.7 ml/lit at 35 DAS + neem (azadirachtin 10,000ppm) @ 3 ml/lit at 50 DAS significantly reduced the yellow mite population. Foliar application of spiromesifen 240 SC @ 0.7 ml/lit at 35 DAS + neem (azadirachtin 10,000ppm) @ 3 ml/lit at 50 DAS was most effective in jute with maximum fibre yield at Barrackpore and Nagaon, respectively